Cuba between hurricanes: commodty frontiers and enviromental challenges - Stubbs, Jean (2021)
In 2017, Hurricane Irma made landfall in Caibarién, in north-central Cuba. Images of a devastated forgotten coastal town catapulted to international prominence a once-thriving port for the export of sugar and sponges, left in the shadows of international tourism on the nearby keys. In 2019, a collaboration between the Commodities of Empire British Academy Research Project, the Antonio Núñez Jiménez Foundation for Nature and Humanity, and the Cuban Film Institute led to filming a documentary in Cuba whose point of departure was Caibarién. The aim was to combine an environmental and commodity frontiers approach to visualize historical junctures and contemporary challenges in the context of global market inequalities and accentuating climate change. Archival research underpinned local testimonies and expert interviews, along with clips from newsreels, documentaries, and feature films, to produce Cuba: Living Between Hurricanes. This article charts the project to film the documentary; homes in on the paradoxes of living first with international tourism, Cuba’s most recent commodity frontier, and then without, due to the Covid-19 perfect storm of a pandemic, likened to a category 5 hurricane; and concludes reflecting on documentary as a tool for raising awareness during the pandemic.